The Influence of Profitability and Good Corporate Governance on Audit Delay (A Study on Trade, Services & Investment Companies Listed on the Indonesia Stock Exchange in 2019–2023) - Shally Khomilah; Irna Maya Sari (Asosiasi Dosen Muda Indonesia, 2025)
This study aims to analyze the effect of profitability and good corporate governance—proxied by the percentage of independent commissioners and the number of audit committee members—on audit delay in trade, services, and investment sector companies listed on the Indonesia Stock Exchange for the period 2019–2023. A total of 23 companies were selected using purposive sampling based on predetermined criteria, resulting in 115 observations from financial and annual reports over five years. The data were analyzed using multiple linear regression with the aid of E-Views 12 software. The results show that profitability and the number of audit committee members have no significant effect on audit delay, while the percentage of independent commissioners has a significant effect in accelerating audit completion.